O que resta do latifúndio - justiça de transição no meio rural paraibano - Santos, Yann Gomes dos (2017)
The present Mater teases "What remains of latifúndio: transitional justice in the rural environment of Paraíba" analyzes the implementation of transitional justice mechanisms in the case of serious violation of human rights committed during the period from 1946 to 1988. In particular, the violations committed by the State during the Military Regime against peasant movements who protested for better work and living conditions, also for access for land (Agrarian Reform as known is Brazil), that movement was known as “Ligas Camponesas”. The teases is guided by the perspective of transitional justice as a mechanism for elaboration of the past, which is based on the research for truth about the period and valorization of memory with the purpose aim of eradicate the apparatuses of state violence. In the case of the Brazilian countryside it is necessary to understand that these violations were caused by a structure that joined private interests that had influence and control over the public apparatus called “latifúndio”, a structure that was strengthened after the military dictatorship, and when the “Ligas Camponesas” were placed in illegality. The research used qualitative methodology with bibliographical and documentary examination to investigate serious violations of human rights through the implementation of justransicional mechanisms in Paraiba, in order to understand the treatment given by the State to these violations. For that, a study about the work of the reparations and truth commissions (the National, the Peasant and State of Paraíba comissions). Finally, an documental investigation is made to understand the relations between the past and present context of violence against the peasants. For that goal we made a research on the annual reports about violence made by the “Comissão Patoral da Terra” in the period between 1986 and 2016 to understand the context of transition from dictatorship to democracy in the countryside or Paraiba.